Regular extra-virgin olive oil intake independently associates with lower abdominal obesity - De Matteis, Carlo; Crudele, Lucilla; Di Buduo, Ersilia; Cantatore, Salvatore; Novielli, Fabio; Cultrera, Silvia; Tricase, Angela Fulvia; Arconzo, Maria; Florio, Marilina; Gadaleta, Raffaella Maria; Piccinin, Elena; Cariello, Marica; et al. (Frontiers in Nutrition, 2025)
BackgroundAbdominal obesity is a major global health burden, driving risk for cardiovascular disease, type 2 diabetes, and cancer. The Mediterranean Diet (MedDiet), recognized for its cardiometabolic benefits, emphasizes Extra-Virgin Olive Oil (EVOO) as a primary fat source. We previously validated the Chrono Med Diet Score (CMDS), an index integrating dietary quality and chrono-nutritional principles, and demonstrated its associations with abdominal adiposity and cancer incidence. Although EVOO is central to the MedDiet, mechanisms related to its specific contributions to metabolic health remain partial. In the present study, we investigated the relationship between consistent EVOO intake frequency, MedDiet adherence (CMDS), and anthropometric outcomes.MethodsWe analyzed data from 16,273 adults (46.5% male) who completed the CMDS-based online survey since April 2023. Data included age, sex, height, weight, waist circumference (WC), Body Mass Index (BMI) and dietary/lifestyle information. EVOO intake frequency was categorized as: sporadic (<3 days/week), frequent (≥3 but <6 days/week), or regular (≥6 days/week), based on 25 g/day ( 2 tablespoons). Statistical analyses included Student’s t-tests, ANOVA with Bonferroni correction, mediation analysis, and multivariable logistic regression adjusting for confounders.ResultsSignificant sex differences were observed in age, BMI, WC, and CMDS. Participants with regular EVOO intake were significantly older (55.9 ± 8.1 years) than sporadic (53.9 ± 7.1) and frequent (54.1 ± 7.7) consumers (p = 0.0019) yet showed more favorable anthropometrics. Compared to sporadic intake, regular intake was associated with significantly lower BMI (24.7 ± 3.0 vs. 26.6 ± 2.9, p < 0.001) and WC (89.1 ± 6.7 cm vs. 99.4 ± 9.1 cm, p < 0.0001), with consistent results across sexes (p < 0.0001 for both). Mediation analysis revealed that EVOO’s effect on WC was significantly mediated by CMDS (β = −0.83, p < 0.0001), accounting for 61.9% of the total effect. A direct association also persisted after adjusting for CMDS (β = −0.59, p < 0.0001). In logistic regression, non-regular EVOO intake was associated with substantially higher odds of abdominal obesity (Odds Ratio 5.1; 95% Confidence Interval: 3.3–6.8; p < 0.0001).ConclusionIn this large cohort, regular EVOO consumption, while defining higher CMDS adherence, is independently associated with lower BMI and WC. EVOO exerts a dual role in metabolic health, both mediating and independently enhancing the relationship between chrono-Mediterranean diet adherence and reduced abdominal obesity. Non-regular EVOO intake emerges as a strong risk factor for visceral adiposity, irrespective of overall diet quality.